2014
DOI: 10.3121/cmr.2014.1236
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Etiologies of Bronchiectasis on the Pulmonary Function Tests

Abstract: Background: Bronchiectasis develops along the natural course of several respiratory and systemic conditions and induces significant changes in the morphofunctional structure of airways. Our objective was to assess the impact of various causes of bronchiectasis on clinical data, pulmonary function tests, and high-resolution computed tomography (HRCT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
1
14
0
3
Order By: Relevance
“…Post‐tuberculosis bronchiectasis patients showed poorer lung function as measured by FEV1%, in contrast to previous reports indicating that there was no difference in lung function between bronchiectasis patients with varying etiologies . Lopes et al suggested that FEV1 values were lower in patients with sequelae of tuberculosis because of greater severity and intensity of bronchial and parenchymal damage . From Table S3, the inflammatory profiles were no significantly different between the groups ( P > .05).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Post‐tuberculosis bronchiectasis patients showed poorer lung function as measured by FEV1%, in contrast to previous reports indicating that there was no difference in lung function between bronchiectasis patients with varying etiologies . Lopes et al suggested that FEV1 values were lower in patients with sequelae of tuberculosis because of greater severity and intensity of bronchial and parenchymal damage . From Table S3, the inflammatory profiles were no significantly different between the groups ( P > .05).…”
Section: Discussionmentioning
confidence: 60%
“…7,8 Lopes et al suggested that FEV1 values were lower in patients with sequelae of tuberculosis because of greater severity and intensity of bronchial and parenchymal damage. 9 From Table S3, the inflammatory profiles were no significantly different between the groups (P > .05). It may be ascribed to two aspects.…”
Section: Discussionmentioning
confidence: 92%
“…Entre os indicadores para a avaliação, destaca-se a capacidade de executar atividades de vida diária (AVD), composta pela avaliação das atividades básicas de vida diária (ABVD), constituídas por comportamentos de autocuidado, e atividades instrumentais de vida diária (AIVD), constituídas por atividades relacionadas à autonomia e participação social (DE OLIVEIRA, 2012;LOPES, 2015). A avaliação da capacidade funcional dos idosos permite conhecer o seu perfil quanto à funcionalidade a fim de promover ações que diminuam as incapacidades inerentes do envelhecimento (FAUSTINO, 2014 A amostra da pesquisa foi de 75 idosos e foi estimada pela demanda do posto de saúde a partir das informações fornecidas pela direção do centro (serviço do HIPERDIA e SÁUDE MENTAL), pelas pesquisas anteriores realizadas com esse público e nas literaturas utilizadas para referenciar o trabalho que incluíam idosos de ambos os sexos.…”
Section: Prefáciounclassified
“…A bronquiectasia é uma doença pulmonar estrutural crônica caracterizada pela dilatação anormal, permanente e irreversível dos brônquios, decorrente da destruição dos seus componentes elásticos e musculares (MENÉNDEZ et al, 2017;LOPES et al, 2015). Clinicamente, a bronquiectasia se manifesta por tosse crônica produtiva, déficit no transporte mucociliar e frequentes exacerbações infecciosas (WEYCKER et al, 2017;, repercutindo em hospitalizações recorrentes e comprometimento da função pulmonar, o que afeta as atividades diárias e a qualidade de vida (WELSH et al, 2015).…”
Section: Introductionunclassified
“…A bronquiectasia é uma doença pulmonar estrutural crônica caracterizada pela dilatação anormal, permanente e irreversível dos brônquios, decorrente da destruição dos seus componentes elásticos e musculares (MENÉNDEZ et al, 2017;LOPES et al, 2015). Clinicamente, a bronquiectasia se manifesta por tosse crônica produtiva, déficit no transporte mucociliar e frequentes exacerbações infecciosas (WEYCKER et al, 2017;, repercutindo em hospitalizações recorrentes e comprometimento da função pulmonar, o que afeta as atividades diárias e a qualidade de vida (WELSH et al, 2015).…”
Section: Introductionunclassified